Evaluación al presupuesto y su ejecución del GAD municipal del cantón Sucúa año 2019 - Alvear Tenempaguay, Berenis Neraida (2021)
ABSTRACT This project aims to determine how the budget execution affects the fulfillment of the budget of the GAD Municipality of Sucúa Canton in 2019. The research work is divided into four chapters, detailed below: Chapter I: In this chapter, the problem statement, justification, general objective, specific objectives, and the hypothesis were developed. Chapter II: The theoretical framework that includes the information regarding the municipality of Sucúa and relevant concepts was established to understand the different terms to be considered in the research. Chapter III: The deductive method was applied. The type of research used was documentary and field, of non-experimental design because there was no manipulation of the information provided by the entity. It is of a quantitative approach and a descriptive research-level since it is described the results obtained. Chapter IV: The results and discussion were established according to the results obtained during the research by applying a survey, budgetary and financial indicators. Chapter V: Finally, the conclusions and their respective recommendations of the research work were established. Keywords: Budget, budget reforms, execution, indicator, income, and expenses. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783